Resistance mechanisms of Cryptococcus spp. and plant compounds as tools to combat them (Research, Society and Development, 2021)
Cryptococcus is a genus of dimorphic basidiomycete fungi found in the form of yeasts and filaments. Cryptococcosis has as main etiological agents the species Cryptococcus neoformans and Cryptococcus gattii. This disease is considered a public health problem and has becoming more alarming because of the limitations of antimicrobials available to its treatment, in addition to an increase in reports of fungal resistance. In this sense, the present review sought to survey information on the resistance mechanisms of Cryptococcus spp. against the main drugs used in cryptococcosis therapy as well as on the antimicrobial activities of plants against these fungi. Studies have reported that several mechanisms may be involved in fungal resistance to drugs including drug inactivation by enzymes, expression of efflux pumps and others drug transporters, as well as changes in the drug target and/or implementation of alternative metabolic pathways. As an alternative to conventional antimicrobials, substances and molecules extracted from plants have demonstrated potential for controlling these pathogens. These phytochemicals can trigger the inhibition and/or death of Cryptococcus through morphological changes on fungi cells, inhibition of ergosterol synthesis, cell leakage, capsular decrease, interference in cell division, reduction of activity of several enzymes such as laccase and urease, inhibition of biofilm formation, among others. In this sense, plants are an important source of bioactive compounds with antimicrobial activity that can be studied in the search for new drugs that are increasingly effective, specific and less toxic in the control of cryptococcosis.